Mass detection on mammograms with image processing techniques and benign-malignant distinction - Karhan, Zehra; Ergen, Burhan; Cetintas, Dilber (IEEE Computer Society, 2014)
In this study, it is aimed the determination of the masses and the masses in mammograms whether benign or malignant is intended to determine. Firstly; was carried out preprocessing on MIAS(Mammogram Image Analysis Society) database of international images. Mass separation was implemented with an appropriate threshold value. Then, Morphological filtering was performed for beter seggmentation. At classification phase, the area covered by the tumor and surrounding area using the criteria irregularity was any distinction between good and evil. At made research were observed more irregular environment of malignant tumors and their areas values certain limits. By using this values, segmented areas are classified as benign and malignant. © 2014 IEEE.
Görüntü işleme yöntemleri ile mamogramlarda kitle tespiti ve iyi-kötü huylu ayirimi
2014 22nd Signal Processing and Communications Applications Conference, SIU 2014 -- 23 April 2014 through 25 April 2014 -- Trabzon -- 106053
Keywords: benign and malignant tumors; mathematical morphological operations; Segmentation